Reporting of Corporate Social Responsibility Practices : An Evidence from Indian BSE-Listed Companies - Behal, VikaS; Gupta, Munish (Prabandhan: Indian Journal of Management, 2022)
CSR activities presently spread across a wide scope of zones including environmental protection and biological protection. As per Section 135 under Schedule VII of Companies Act (2013) in Indian context, it furnishes that each organization in India with a total asset holding exceeding or equals to ₹five hundred crore rupees or an annual sales of exceeding or equals to ₹1000 crores rupees or a net profit of more than or equals to ₹5 crore rupees for any one financial year is required to establish a Corporate Social Responsibility Committee. Using the sample of BSE listed corporates across several industrial sectors in India, the objective of the study is to investigate whether there is an improvement in the corporate social responsibility scores of companies over the predetermined time range (from 2014-15 to 2019-20). Application of paired samples t-test as to test whether the mean difference between two groups is significantly different from zero indicates interesting CSR based outcomes for the items designed under CSR checklist. The derived findings were also found to be robust to the application of non-parametric statistical testing technique. It has generated suitable research insights for the academicians and policy makers of Indian corporate sector and will facilitate them to establish appropriate CSR norms to be applicable in India